SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN DESA PETANI TERBAIK MENGGUNAKAN METODE FUZZY MODEL TAHANI - Ervina, Nina; Nasution, Surya Darma (TIN: Terapan Informatika Nusantara, 2020)
Indonesian is an agricultural country that produces a wide variety of agricultural and plantation products, one of which is agricultural production which is fruit trees. Fruits are an export commodity developed by the government to accompany the cultivation of food crops because of the production that has the opportunity to get greater profits. Deli Serdang Regency is a district where many people are farmers, especially in the Lubuk Pakam sub-district which consists of several villages which constitute the main income from agricultural products and livestock products, the district of Deli Serdang bordering the north with Langkat and Straits of Malaka, south with Karo District and Simalungun Regency, east of Serdang Bedagai Regency and on the west bordering Karo District and Langkat District, there are 22 sub-districts in Deli Serdang District which are each sub-district which is a large number of farming communities. For this reason, we need a system that can help sub-district leaders in making decisions to determine the best farmer villages in accordance with what is expected from the sub-district for rural villages that are in accordance with predetermined criteria. Due to the problem, it is necessary to design a decision support system using the Tahani model fuzzy database method to assist in selecting the best farmer villages in Lubuk Pakam District. Hopefully with the application of the support system decision for the selection of the best farmer villages, it is expected to be able to help with decision making or as a recommendation for villages selected in Lubuk Pakam sub-district